PROSTATE CANCER WITH A HIGH BASELINE PSA LEVEL AFTER COMBINED TREATMENT - A. T. Asratov; A. S. Kalpinskiy; I. A. Taraki; Yu. V. Samsonov; A. A. Kostin (Исследования и практика в медицине)
This article describes a rare clinical case of prostate cancer with a high baseline PSA level of 1407 hg/ml. In the course of diagnosis, hormonal and surgical treatment there was a successive dynamics of PSA decline: 07.08.2015–1407 ng/ ml, 14.09.2015–43,61ng/ml; 17.11.2015–0,326 ng/ml; 13.02.2016 (end of hormone therapy) — 0,084 ng/ml. After the operation of radical prostatectomy with enlarged lymphadenectomy, on 20.04.2016 (with prolonged hormone therapy up to 9 monthes) gradual decrease of PSA level continued: 05.05.2016–0,008 ng/ml; 17.06.2016–0,008 ng/ml; 08.09.2016–0,039 ng/ml; 30.11.2016–0,002 ng/ml; 07.09.2017 (total PSA) — 0,008 ng/ml. In parallel, there was a consistent improvement in the clinical picture, up to the MRI data of 19.10.2017, when there were no significant neoplastic changes at the level of the study (in the projection of the prostatic bed).